Disposable plastic trays and their effect on polyether and vinyl polysiloxane impression accuracy: an in vitro study - Rues, Stefan; Stober, Thomas; Bargum, Thomas; Rammelsberg, Peter; Zenthöfer, Andreas (Clinical oral investigations, 2021)
To evaluate the dimensional accuracy of impressions taken by use of disposable stock plastic trays and to compare performance with that of metal trays.